Low-temperature universal dynamics of the bidimensional Potts model in the large q limit. (10th September 2021) - Chippari, Francesco; Cugliandolo, Leticia F; Picco, Marco
Abstract: We study the low temperature quench dynamics of the two-dimensional Potts model in the limit of a large number of states, q ≫ 1. We identify a q -independent crossover temperature (the pseudo spinodal) below which no high-temperature metastability stops the curvature driven coarsening process. At short length scales, the latter is decorated by freezing for some lattice geometries, notably the square one. With simple analytic arguments, we evaluate the relevant time-scale in the coarsening regime, which turns out to be of Arrhenius form and independent of q for large q . Once taken into account, dynamic scaling is universal.